Peperangan Siber dalam Perspektif Geografis: Tinjauan terhadap pendekatan berbasis GEOINT - Muhammad Thafshir Triansha; Asep Adang Supriyadi; Syachrul AriefArief; Yosef Prihanto (UNIB Press, 2026)
This literature review examines the emerging integration between geospatial intelligence (GEOINT) and cyber warfare through an analysis of 23 peer-reviewed publications. The study traces the application of geospatial technologies, including Geographic Information Systems (GIS), spatial analysis, and geographic profiling, within cyber operations for threat detection, attribution, and strategic planning. The findings indicate that geographic profiling can associate up to 82 percent of cyber threats with recognizable spatial patterns, while spatio-temporal analysis provides insight into attack distribution patterns and their attribution processes. The reviewed studies demonstrate the relevance of GEOINT in military operations, critical infrastructure protection, and national security contexts. The analysis also reveals several limitations in the existing body of knowledge, particularly the absence of standardized frameworks, validated methodologies, and policy guidelines for GEOINT and cyber integration. The contribution of this review lies in synthesizing the existing empirical evidence, assessing methodological developments, and identifying research gaps that require further investigation. Its originality rests on presenting an assessment specifically directed at GEOINT-based approaches within cyber warfare research, a topic that remains underrepresented in the current literature.